A PRELIMINARY MOLECULAR ASSESSMENT OF THE TAXONOMIC VALIDITY OF Hexagenia orlando TRAVER, 1931 (EPHEMEROPTERA: EPHEMERIDAE) - Alexander B. Orfinger (Genetics & Applications, 2020)
In an effort to evaluate the taxonomic uncertainty of the species status of Hexagenia orlando Traver, 1931 (Ephemeroptera: Ephemeridae), molecular data were used for the first time to test its current classification. Mitochondrial cytochrome c oxidase subunit I (COI) haplotypes were evaluated using three types of analyses in the form of distance-based, tree-based, and model-based delimitation methods. All analyses consistently recovered H. orlando as a valid species. These preliminary results lend evidence reinforcing the current classification scheme and encourage renewed scrutiny of adults and nymphs to hopefully identify additional morphological characters that may serve to separate H. orlando and its congener Hexagenia limbata (Serville, 1829).